Isolated Port-Site Metastases After Minimally Invasive Hysterectomy for Endometrial Cancer: Outcomes of Patients Treated With Radiotherapy. Issue 5 (1st June 2015) - Grant, Jonathan Douglas; Garg, Amit K.; Gopal, Ramesh; Soliman, Pamela T.; Jhingran, Anuja; Eifel, Patricia J.; Klopp, Ann H.
Abstract : Objective: The management and prognosis of isolated port-site metastases after laparoscopic surgery for endometrial cancer is poorly understood and rarely described in the literature. We report a series of cases treated with radiotherapy to better characterize outcomes in these patients. Methods: We retrospectively reviewed medical records of patients with endometrial cancer who developed isolated port-site metastases and were treated with radiation therapy at MD Anderson Cancer Center from 1996 to 2013. Seven patients met these criteria for whom treatment and outcome data were collected. Results: The median interval from initial surgery to port-site recurrence was 15 months. Recurrent tumor size varied from 0.5 to 9 cm as measured on axial imaging. Six of the 7 patients underwent surgical resection of the recurrence. All received radiotherapy to a dose of 45 to 66 Gy. At a median follow-up of 2 years from the time of the port-site recurrence, the rate of disease-free survival at 1 and 2 years after the recurrence was 100% and 44%, respectively. The rate of local control and overall survival at 2 years was 100%. Conclusions: Isolated port-site metastases in the setting of endometrial cancer are associated with high rates of local control when treated with multimodality therapy including radiotherapy. Long-term disease-free outcomes in some patients suggest the potential for cure and justify aggressive local therapy. The optimal integration of surgery, chemotherapy, and radiation is unknown.